Multi-Track Diplomacy of Indonesian to Promoting Tourism in the United States during Covid-19 Pandemic - Fatmawati; Saktia Aprianto Putra (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
The emergence of Covid-19 pandemic at the end of the year 2019 has made Indonesia’s tourism sector one of the most affected. The most important impact is decrease in number of tourist arrivals from the United States, which is one of Indonesia’s tourism partners. The paper aims to describe multi-track diplomacy of Indonesian to promoting tourism in the United States during Covid-19 Pandemic. Descriptive analysis with qualitative research and secondary data applied in this research. Through multi track diplomacy, promotion of Indonesian tourism in.1the United States during Covid-19 pandemic involved important actors, such as the ministry of tourism and creative, KJRI in the United States, activists, travel agents, airlines, Majelis Ulama Indonesia, private citizen, and various media intermediaries